PENGARUH PENGGUNAAN HORMON 2,4-D DAN KINETIN TERHADAP PERTUMBUHAN KULTUR EMBRIO JERUK KUOK (Citrus nobilis Lour) SEBAGAI RANCANGAN HANDOUT BIOLOGI DI SMA - Romita Romita; Imam Mahadi; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is aim to know the effect of 2,4-D and Kinetin for the growth of embryo culture Orange Kuok (Citrus nobilis Lour) and to design source learning in form of handout. The study is doing in Laboratory of Biology Education FKIP University of Riau and Laboratory Biotechnology of Islamic University Riau from April – June 2017. This Study using complete randomized design factorial by 5 x 5 with three repetition. First factor 2,4-D (D) consist of 5 level: 0 mgl-1, 1 mgl-1, 2 mgl-1, 3 mgl-1 , dan 4 mgl-1. Second factor Kinetin (K) consist of level: 0 mgl-1, 1 mgl-1, 2 mgl-1, 3 mgl-1 , dan 4 mgl-1. Measured parameters is time of bud appear, percentage of explan life, time of roots appear, number of bud, number of roots, and high of bud. The data is analyze using ANAVA and further test with DNMRT on 5%. Result of this study show effect 2,4-D and Kinetin have significantly impact on growth of embryo Orange Kuok. Combination of 2,4-D and Kinetin show fastest appearing of bud is on D4K3 7 day after culture treatment compared with D0K0 9,67 day after culture, Combination 2,4-D and Kinetin show that 11 treatment have 100% life percentage D1K4, D2K2, D2K3, D2K4, D3K2, D3K3, D3K4, D4K1, D4K2, D4K3, D4K4, Combination 2,4-D and Kinetin show fastest appearing of roots on D4K4 treatment 7,67 day after culture, Combination 2,4-D and Kinetin show the highest number of bud in the treatment D4K3(4.67), Combination of 2.4-D and Kinetin showed the highest number of roots in the treatment of D4K3 (7), Combination 2.4-D and Kinetin showed the highest bud height that is in treatment D4K3 (4.33 cm). The results of this study can be used as a design of learning resources in the form of handouts in the concept of modern biotechnology class XII Senior High School.Keywords : 2,4-D, Kinetin, Embryo Culture, Handout